Efektivitas Kombinasi Endorphine Massage Dan Aromaterapi Lemon Terhadap Intensitas Nyeri Pada Ibu Bersalin Kala I - Yohana Putri Apryanti; siti choirul dwi astuti (POLTEKKES KEMENKES MANADO, 2020)
Background : Pain is a physiological thing that will be faced by a maternity mother. Pain is a sensory experience. Research published by the Journal of Physiotherapy proves that massages performed for 30 minutes at the opening of the cervix 4-5cm during uterine contractions can decrease the intensity of pain. Similarly, research published by the Pasific Journal of Tropical Biomedicine explains that the inhalation of essential oils can stimulate olfactory bulbs to provide comfort. Purpose: this study was conducted to identify the decrease in pain intensity in maternity mothers who were given treatment and not given endorphine massage method treatment and lemon aromatherapy. Method: This research was conducted using the research design pseudo experiments (Quasy Experiments) with the design used is pretest-post test control group design. Sampling technique is puprposive sample as many as 30 respondents in BPM working area of Puskesmas Simalingkar which is divided into 15 respondents as an intervention group and 15 respondents as a control group Results: research shows the intensity of pain in the intervention group is more decreased compared to the intensity of pain in the control group. So as a rekomendasu for health workers to be able to provide these two therapies in helping mothers reduce the pain of childbirth